Dissecting kinetic pathways to formation of the fibrillar objects in molecular gels using synchrotron FT-IR. Issue 42 (1st July 2015) - Rogers, Michael A.; Liu, Xia; Mallia, V. Ajay; Weiss, Richard G.
Abstract : Infra-red synchrotron radiation is used to monitor the formation of fibrillar networks as sols of simple gelators become gels. Abstract : The processes associated with sol-to-molecular gel transitions are often difficult to follow in real time due to the characteristically short time-frames for pseudo-crystallization leading to fibrillar objects and establishment of their 3-dimensional networks. We use fast infrared spectroscopic methods to overcome these difficulties in a 'demonstration of principle' study: the nucleation and growth of crystallites of two amide derivatives of ( R )-12-hydroxystearic acid, ( R )-12-hydroxy- N -propyloctadecanamide (1 ) and ( R )-12-hydroxyoctadecanamide (2 ), in mineral oil over a range of temperatures. First, the gel properties were established by optical microscopic, differential scanning calorimetric, and rheological measurements. Thereafter, the environments experienced by individual functional groups within1 and2 have been followed as a function of gelation time, and the data were treated by Avrami and fractal models in order to extract the kinetics, activation energies, and natures of the growth processes. The data both provide insights and raise new questions concerning the manner by which the amide and hydroxyl groups interact over the critical time periods during which the fibrillar networks of the gels are being established. The results demonstrate the utility of fast infrared spectroscopy as a valuable new tool to probe intimate details of the processes associated with self-assembly. The techniques and methodologies described are amenable to use with a wide range of gelating (or other aggregating) systems.